A study on operation control of urban centralized heating system based on cyber-physical systems. (15th January 2020) - Lin, Xiaojie; Liu, Sibin; Lu, Shuowei; Li, Zhongbo; Zhou, Yi; Yu, Zitao; Zhong, Wei
Abstract: Intelligent and efficient operation of large-scale urban centralized heating system (UCHS) is a hot topic in urban energy system field. This study develops an intelligent operation control platform for China's UCHS via "cyber-physical systems" (CPS). The platform is based on graph theory and thermal-hydraulic modeling and has been validated against measured data collected from the substations. 88.5% of the modeled substation supply pressure has an error of less than 5%, and 82.1% of the modeled substation return pressure has an error of less than 5%. The platform carries out "model-based prediction" and "prediction-based decision-making" by incorporating state sensing, load forecasting, modeling, and model-based operation optimization. The platform is further applied to a target UCHS using coal-based combined heat and power (CHP) units and gas-fired boilers as heating sources and covering an area of 15 million m 2 . To ensure the accuracy, this study carries out online calibration with real-time operation data and tests the load distribution feature during the pilot heating season. During a two-day operation, the optimized heating sources load distribution scheme could reduce natural gas consumption by up to 31.2% when compared with existing experience-based operation. The operation cost during that operation period is also reduced by 2.6%, accordingly. Highlights: "Cyber-physical systems" idea is applied to urban centralized heating system. A CPS-based control platform is developed and further tested in a real site. The platform reduces overall energy consumption during pilot season testing.